Deposição de nanocristais coloidais: da síntese à aplicação na fotoeletroquímica da oxidação da água - Gonçalves, Ricardo Henrique (2016)
An excellent and potentially efficient route towards storing solar energy is to convert light into chemical energy in the form of chemical bonds, which is a form of artificial photosynthesis. Considering the abundance of H2O on the planet, water splitting is a natural pathway for artificial photosynthesis. Hematite is an n-type semiconductor with high chemical stability in alkaline media and promising material for photoelectrochemical water splitting. This Thesis describes critical parameters involved in the Colloidal Nanocrystals Deposition (CND) process to produce hematite photoanodes with high efficiency for solar-to-hydrogen conversion. In chapter 2, a fundamental study reveals that the interface solid-solid is a parameter that has strong influence on the performance of the photoanode. The gap between the FTO substrate and hematite thin film was observed by HRTEM image and it can be overcome during a sintering stage. In the same chapter, the solid-solid interface analysis was correlated with the photoresponse and it has showed that hematite thin film treated at 1000 oC also improved the response of this photoande. This result was explained based on the grain growth and associated with the mass distribution on the FTO surface. In chapter 3, the CND process was improved using the magnet to assist the nanocrystals deposition and also oxidation of magnetite (Fe3O4) to maghemite (γ- Fe2O3) to avoid the presence of Fe2+. In this approach, Sn4+ was used as a doping element and has showed a significant improve on the photoresponse of the hematite. The STEM-EDS analysis has showed that Sn has ability to segregate on the hematite grain boundary during sintering process, blocking grain growth process. The results showed in chapter 4 were essential to understand the thickness effect on the photocurrent of thin film produced by CND process. In this case, changing the nanocrystals concentration has direct effect on the thickness of the hematite thin film. The FTO roughness also showed significant influence on the orientation of hematite grain along the direction <110>. In this study, it was possible to calculate the maximum theoretical efficiency for the hematite photoanode obtained by this method. The thickness control and homogeneity of the thin film give a great perspective for technological application of this process. The in situ heating TEM demonstrated that nanocrystals has abnormal grain growth and also a superplastic phenomenon, as revealed in chapter 5. In this chapter, Sn was deposited on γ-Fe2O3 impeding atom dislocation on the grain boundary and consequently inhibits the growth process. This experiment was an approach to simulate the sintering process performed in the CND process. The electrocatalyst described in chapter 6, showed low overpotential for OER. The strategy to use a Prussian blue analogue to deposit a thin layer of nickel-iron hexacyanoferrate and convert into oxyhydroxide achieved excellent homogeneity and low overpotential for OER. This result is comparable with IrO2 and RuO2 that are electrocatalysts with high electrochemical performance. Catalyst supports were also evaluated, such as FTO, palladium and PGS. The PGS substrate showed an excellent performance as catalytic support for OER, with similar results of palladium foil.